Binary Opposition in Narrations of â€œNativeâ€ in Social Media - Puspitasari Puspitasari (Ikatan Sarjana Komunikasi Indonesia, 2018)
The â€œnativeâ€ or pribumi term as a narrative emerged into the public sphere and raises questions since October 16, 2017, whether the term is merely a conversation on the surface or more deeply describes the narrative that represents the socio-cultural aspect of Indonesian society. The study was conducted using twitter as a locus of observation within the period of November 8-16, 2017. Based on the idea that a social text reflects a narrative building constructed socio-cultural and leaves a long history trail, preliminary findings indicate that Indonesian society has a historical heritage of Dutch colonialism on native and non-native (Chinese/Tionghoa). The